Impact of an in-built monitoring system on family planning performance in rural Bangladesh - Ashraf Ali; Gazi Rukhsana; Kabir Humayun; Saha Nirod (BMC, 2007)
Abstract Background During 1982-1992, the Maternal and Child Health Family Planning (MCH-FP) Extension Project (Rural) of International Centre for Diarrhoeal Disease Research, Bangladesh (ICDDR,B), in partnership with the Ministry of Health and Family Welfare (MoHFW) of the Government of Bangladesh (GoB), implemented a series of interventions in Sirajganj Sadar sub-district of Sirajganj district. These interventions were aimed at improving the planning mechanisms and for reviewing the problem-solving processes to build an effective monitoring system of the interventions at the local level of the overall system of the MOHFW, GoB. Methods The interventions included development and testing of innovative solutions in service-delivery, provision of door-step injectables, and strengthening of the management information system (MIS). The impact of an in-built monitoring system on the overall performance was assessed during the period from June 1995 to December 1996, after the withdrawal of the interventions in 1992. Results The results of the assessment showed that Family Welfare Assistants (FWAs) increased household-visits within the last two months, and there was a higher use of service-delivery points even after the withdrawal of the interventions. The results of the cluster surveys, conducted in 1996, showed that the selected indicators of health and family-planning services were higher than those reported by the Bangladesh Demographic and Health Survey (BDHS) 1996-1997. During June 1995-December, 1996, the contraceptive prevalence rate (CPR) increased by 13 percentage points (i.e. from 40% to 53%). Compared to the national CPR (49%), this increase was statistically significant (p < 0.05). Conclusion The in-built monitoring systems, including effective MIS, accompanied by rapid assessments and review of performance by the programme managers, have potentials to improve family planning performance in low-performing areas.